Analisis Pengaruh Pertumbuhan Ekonomi, Foreign Direct Investment dan Konsumsi Energi Terhadap Kualitas Lingkungan di Indonesia : Ditinjau Dari Emisi Karbon Dioksida (CO2) - Lesmana, Indra; Astuty, Sri; Jamil, Muh. (Jurnal EMT KITA, 2024)
This research aims to determine the influence of economic growth, foreign direct investment and energy consumption on environmental quality in Indonesia in terms of increasing carbon dioxide (CO2) emissions. This research is descriptive quantitative research with multiple linear regression analysis tools using the e-Views 12 application. The data used in this research is time series data with a period of 38 years in the period 1985-2022 obtained from various sources on the internet including Worldbank, Global Carbon Atlas, and Our World In Data. The research results show that economic growth has a negative and insignificant influence on environmental quality in Indonesia. If economic growth increases by 1%, it will reduce CO2 emissions by 1.42%. Furthermore, FDI and energy consumption have a positive and significant influence on environmental quality in Indonesia. If FDI and energy consumption increase by 1%, then these two variables will increase CO2 emissions by 2.67% and 0.26%. Simultaneously economic growth, FDI and energy consumption have a positive and significant influence on environmental quality in Indonesia in terms of CO2 emissions.